The Relation between Contraception Methods and Quality of Life (Epidemiology, Biostatistics, and Public Health, 2022)
Objectives:  Assess the relationship between contraception methods and quality of life in women of reproductive age.Methods: This cross sectional study was conducted in Gonabad, Iran. Multi-stage sampling method was used to select 18-45 year-old women with using a contraceptive methods during the last six months. Demographic and the Short Form 36 (SF-36) Quality of Life Questionnaires were used for data collection. For statistical analysis the Stata11 and SPSS16 software were used. The level of significance was set at P < 0.05. After performing different statistical tests in bivariate analysis, the multi-variable linear regression was used to assess the association between method of contraception and domains of quality of life adjusting for other confounding factorsResults: Women with Tubal sterilization had significant worse “physical functioning” [adjusted regression coefficient=-5.14 (95%CI:-10.2 to -0.01)] but better “general health perceptions” [adjusted regression coefficient=6.8(95%CI: 2.1 to 11.5)] than those preferring male condom (reference). Women whose husbands had vasectomy had also on average significant better score of “general health perceptions” than condom users (reference) [adjusted regression coefficient=7.1(95%CI: 0.23 to 14)]. Withdrawal showed on average higher score of “vitality” than condom users (reference) [adjusted regression coefficient=25.07(95%CI: 7.44 to 42.6)].Conclusion: The results showed that some aspects of women's quality of life could be affected by using different contraception methods.